Implementasi Kebijakan Penuntasan Buta Aksara Al-Qur’an Di Kecamatan Meral Barat Kabupaten Karimun - Muhamad Firdaus; Agus Hendrayady; Okparizan Okparizan (Perkara : Jurnal Ilmu Hukum dan Politik, 2023)
The Al-Qur'an Literacy Completion Policy is a policy that aims to change people's attitudes or behavior. There are still many obstacles to the implementation of the Al-Qur'an illiteracy eradication policy, therefore the support from related parties is needed. The purpose of this study was to find out the implementation of the district head's decree no 123 A of 2006. The informants in the study were parties involved in implementing the Al-Qur'an illiteracy policy, teachers and the community as parents of the Santri in Meral Barat District. Data analysis techniques in this study using triangulation techniques. The results of this study are seen from the dimensions of the content of the policy, the formation of this policy on the basis of meeting the needs of the community and the local government's concern for changing people's behavior and making people good at reading, understanding and practicing the contents of the Al-Qur'an. This policy is considered appropriate to be implemented in Karimun which is cultured with Malay. Human resources and infrastructure then influence the implementation of this policy. From the analysis of the environmental dimensions of the policy, the program implementers are trying to overcome every obstacle, even though it is not yet optimal, such as diverting study hours for Santri as needed and making other religious programs. So, the characteristics of the BMPG-TPQ of West Meral District is an institution under the supervision of the BMPG-TPQ of Karimun Regency which handles the management of TPQ in Karimun Regency.